Development of Methods of Quality Control of the Tablets «Ramipril» - Kateryna Typlynska; Yuliya Kondratova; Liliya Logoyda (MDPI AG, 2023)
Our main target was to develop methods for the quality control of the tablet «ramipril» according to the indicators of «Quantitative determination», «Impurities» and «Dissolution». New, precise, accurate and green HPLC methods were developed for the determination of ramipril and its impurities in tablets. The separation was accomplished using a diode array detector at 210 nm with an isocratic and gradient mobile phase consisting of a 0.2 g/L solution of sodium hexanesulfonate (pH 2.7) and the acetonitrile and chromatographic columns Acclaim 120 C18 and Inertsil ODS-3. The developed method was validated in accordance with ICH guidelines. The analysis of impurities was performed within a run duration of less than 25 min, which is about a two times shorter than that of the official Ph. Eur. method. The analysis of ramipril in tablets was performed with a run duration of less than 4.5 min, which is about three times shorter than that of the official USP method. The developed methods were successfully applied for the quality control of the tablet «ramipril» according to the indicators of «Quantitative determination», «Impurities» and «Dissolution». In addition, they proved its superiority over the reported methods in terms of greenness using different assessment tools.